A role for PchHI as the ABC transporter in iron acquisition by the siderophore pyochelin in Pseudomonas aeruginosa. (18th October 2021) - Roche, Béatrice; Garcia‐Rivera, Mariel A.; Normant, Vincent; Kuhn, Lauriane; Hammann, Philippe; Brönstrup, Mark; Mislin, Gaëtan L. A.; Schalk, Isabelle J.
Summary: Iron is an essential nutrient for bacterial growth but poorly bioavailable. Bacteria scavenge ferric iron by synthesizing and secreting siderophores, small compounds with a high affinity for iron. Pyochelin (PCH) is one of the two siderophores produced by the opportunistic pathogen Pseudomonas aeruginosa . After capturing a ferric iron molecule, PCH‐Fe is imported back into bacteria first by the outer membrane transporter FptA and then by the inner membrane permease FptX. Here, using molecular biology, 55 Fe uptake assays, and LC–MS/MS quantification, we first find a role for PchHI as the heterodimeric ABC transporter involved in the siderophore‐free iron uptake into the bacterial cytoplasm. We also provide the first evidence that PCH is able to reach the bacterial periplasm and cytoplasm when both FptA and FptX are expressed. Finally, we detected an interaction between PchH and FptX, linking the ABC transporter PchHI with the inner permease FptX in the PCH‐Fe uptake pathway. These results pave the way for a better understanding of the PCH siderophore pathway, giving future directions to tackle P. aeruginosa infections.